2019
DOI: 10.1007/978-3-030-33742-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Implementing AI Ethics in Practice: An Empirical Evaluation of the RESOLVEDD Strategy

Abstract: Use of artificial intelligence (AI) in human contexts calls for ethical considerations for the design and development of AI-based systems. However, little knowledge currently exists on how to provide useful and tangible tools that could help software developers and designers implement ethical considerations into practice. In this paper, we empirically evaluate a method that enables ethically aligned design in a decision-making process. Though this method, titled the RESOLVEDD strategy, originates from the fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…When designing a programme of research, the choice of which method to employ is dependent upon the nature of the research problem (Noor 2008). If our intention was to develop an in-depth understanding of how one method for translating ethics principles into practice might become effective, then a case study approach would be most appropriate, as demonstrated by Vakkuri and Kemell (2019) in their review of the RESOLVEDD strategy for ethical decision-making, or Wong et al (2018) in their evaluation of mobile Augmented Reality (AR) learning trails-Trails of Integrity and Ethics-in Hong Kong. Alternatively, a scoping or systematic review approach could be appropriate, as Nicholls et al (2015) highlighted with their review of empirical research assessing the quality and effectiveness of research ethics reviews.…”
Section: Methodsmentioning
confidence: 99%
“…When designing a programme of research, the choice of which method to employ is dependent upon the nature of the research problem (Noor 2008). If our intention was to develop an in-depth understanding of how one method for translating ethics principles into practice might become effective, then a case study approach would be most appropriate, as demonstrated by Vakkuri and Kemell (2019) in their review of the RESOLVEDD strategy for ethical decision-making, or Wong et al (2018) in their evaluation of mobile Augmented Reality (AR) learning trails-Trails of Integrity and Ethics-in Hong Kong. Alternatively, a scoping or systematic review approach could be appropriate, as Nicholls et al (2015) highlighted with their review of empirical research assessing the quality and effectiveness of research ethics reviews.…”
Section: Methodsmentioning
confidence: 99%
“…Within the frameworks that guide AI’s development, the question remains: Who is in charge or responsible for ethically aligning AI in healthcare? Empirical evidence suggests that development teams are often more concerned with the usefulness and viability of the product rather than its ethical aspects [ 35 ]. In part, these results are expected as software developers are not responsible for strategic decisions regarding how and why AI is developed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…If all the organization has is a set of principles that do not change its daily practices, they are of little practical effect. This "principles-to-practice" quandary is a recognized problem in the literature, and while many researchers have proposed solutions that include frameworks, toolkits, and guidelines [5,6,[49][50][51], their lack of organizational adoption persists [33,[52][53][54].…”
Section: A Gap 1 -Ai Ethical Principles -> Ai Ethical Practicesmentioning
confidence: 99%
“…Based on the literature, many frameworks, toolkits, and guidelines have linked AI Ethical Principles to proposed AI Ethical Practices. These included the IEEE's Ethically Aligned Design principles [5] for AI system design, Shneiderman's [6] fifteen proposals for bridging the gap between ethics and practice using an enhanced governance approach, Peters et al's [50] proposal for balancing a responsible design process with the user's interaction with the technology, and Vakkuri and Kemell's [51] nine-step "RESOLVEDD strategy" for rational ethical decision-making. These various approaches form the foundation for part of the problem space that the RRD can address.…”
Section: A Ai Ethical Principles To Practicesmentioning
confidence: 99%